Nonviolent Offenders' and College Students' Attachment and Social Support Behaviors: Implications for Counseling - Hawkins-Rodgers, Yolanda (International journal of offender therapy and comparative criminology, 2005)
This study examines the relationships between adult attachment orientations and the ability to seek social support as factors in mediating behavior. Data were collected on non violent offenders (n = 57) and college students (n = 89). The results indicated the non-normative group of nonviolent offenders reported being more securely attached and having more satisfaction with their social supports than the normative group of college students. Fewer college students reported being securely attached than the nonviolent offenders but had a larger number of social supports. In the insecure categories, nonviolent offenders reported being more dismissively attached whereas college students reported being preoccupied in their attachment orientation. The study suggests that attachment and social-support-seeking behaviors across different populations may be potential factors in designing counseling services that are used for risk classification and needs assessment